Penerapan Algoritma Feature Selection Chi-Square (X2) Dalam Sistem Monitoring Tumbuh Kembang Balita - Khozainuz Zuhri; Fatimah Fahurian; Yodhi Yuniarthe (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2020)
The healthy family program is a priority program of the ministry of health which in principle refers to the 5th nawacita program. In line with this program, the Lampung provincial government has launched development in the health sector in all cities or districts by allocating 11.52% of the special budget for the health sector. This is inseparable from the condition of health development, especially the city of Bandar Lampung, where the infant mortality rate, under-five mortality rate and maternal mortality rate are decreasing. One of the conditions of health development is the health service posts. Health service posts have limited medical personnel and health post data searches still use conventional models so that the results obtained are not optimal. Based on these descriptions, the authors propose to design a software engineering system in the field of medical health in the form of a toddler growth monitoring system with the concept of the Chi-Square or X2 feature selection algorithm. The results of this study are able to provide a web-based monitoring system model that can be accessed anywhere and anytime, able to provide a system model that can directly monitor the condition of toddler health growth and is able to provide a system model that can be used by health workers, both medical and midwives to monitor village health post points.